Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

How would I verify the following double angle identity. $$ \sin(A+B)\sin(A-B)=\sin^2A-\sin^2B $$ So far I have done this. $$ (\sin A\cos B+\cos A\sin B)(\sin A\cos B-\cos A\sin B) $$But I am not sure how to proceed.

share|improve this question
add comment

6 Answers 6

\begin{eqnarray} \sin(A+B)\sin(A-B) &=& (\sin A\cos B+\cos A\sin B)(\sin A\cos B-\cos A\sin B)\\ &=& \sin^2 A \cos^2 B -\sin^2 B \cos^2 A\\ &=& \sin^2 A \cos^2 B -\sin^2 B (1-\sin^2 A)\\ &=& \sin^2 A (\cos^2 B + \sin^2 A) - \sin^2 B\\ &=& \sin^2 A - \sin^2 B \end{eqnarray}

share|improve this answer
    
It makes sense.Thank you. –  El Bananero Jul 25 '12 at 17:47
add comment

$$ \begin{align*}\sin (A+B)\cdot\sin (A-B)&=\frac{\cos(2B)-\cos (2A)}{2}\\&=\frac{(1-2\sin^2B)-(1-2\sin^2A)}{2}\\&=\sin^2A-\sin^2B\end{align*}$$

Here i have used $$\sin x\cdot\sin y=\frac{\cos(x-y)-\cos(x+y)}{2}$$

share|improve this answer
add comment

Hint: $(a+b)(a-b)=a^2-b^2$.
Then use $\sin^2\theta+\cos^2\theta=1$

share|improve this answer
    
Do you mean I would do (sinA-sinB)(SinA+sinB)? –  El Bananero Jul 25 '12 at 17:38
    
No, $a=\sin A \cos B$ and $b=\sin B \cos A$ –  Saurabh Jul 25 '12 at 17:40
    
Oh I see thanks. –  El Bananero Jul 25 '12 at 17:47
add comment

use this formula

$$ 2Sin(A+B)Sin(A-B)=Cos2B-Cos2A $$

it will like this

$$ 1/2 * (Cos2B-Cos2A) $$ $$ \frac {(1-2Sin^2B)-(1-2sin^2A)}{2} $$

it will give answer

share|improve this answer
add comment

Open the bracket of what you got and substitute every cos^2 with 1-sin^2 and open bracket again. Thats it...

share|improve this answer
add comment

Your question involves the basic algebra identity which says, $(a + b)(a - b) = a^2 - b^2 $. For targeting your question, it is easy to assume $ a = \sin A\cos B $ and $b = \cos A \sin B$. The process becomes easy now.

$$\begin{align}(a + b)(a - b)& =& a^2 - b^2\\ & = & (\sin A \cos B)^2 - (\cos A \sin B)^2\\ & = & \sin^2A\cos^2 B - \cos^2A\sin^2B \\ & = & \sin^2A(1 - \sin^2 B) - \cos^2 A\sin^2B \end{align} $$Proceed.

share|improve this answer
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.